TEXT AND DATA MINING IN TERMS OF INTELLECTUAL PROPERTY - Küçükali, Canan (International Scientific Journal Vision, 2023)
With the intense penetration of the internet into our lives, sharing has increased worldwide, whether in intellectual property or industrial property, as in other fields. Text and data mining has become an area for supporting experts working in the field of intellectual property, facilitating the work of decision- makers, and helping them in solving problems. While data mining activities are involved different issues such as copyright, database rights, and data protection, text and data mining activities that are not regulated in TRIPS and international agreements are discussed as to whether they cause violations or not. The problem in this matter is tried to be solved differently in each legal system by being evaluated within the scope of fair use in US law and by being included in the scope of the Directive in EU law. However, both EU law and other laws have areas that need to be renewed in the face of technological developments.